Clinically isolated aortitis presenting as inferior ST-elevation myocardial infarction due to an unruptured sinus of Valsalva aneurysm: a rare and forgotten cause of acute coronary syndrome in a young patient with no evidence of systemic vasculitis. Issue 5 (24th May 2021) - Baqi, Abdul; Shams, Pirbhat; Ahmed, Intisar; Tariq, Muhammad
Abstract : A 21-year-old man presented with chest pain, diaphoresis and dyspnoea. Electrocardiogram (ECG) showed inferior ST-elevation myocardial infarction. Troponin I was positive. Patient underwent left heart catheterisation, which revealed normal epicardial coronary arteries except for right coronary artery which could not be engaged. CT coronary angiogram was done, which revealed large right sinus of Valsalva aneurysm giving rise to a pinched out right coronary artery. Patient underwent composite graft replacement of aortic valve, aortic root and ascending aorta along with a saphenous vein graft to right coronary artery. He was discharged in stable condition on fifth postoperative day. Biopsy of the aneurysmal tissue was suggestive of vasculitic aetiology. There was no evidence of systemic vasculitis and Magnetic Resonance Angiography (MRA) screen was negative for Takayasu's arteritis. Our patient was, hence, diagnosed with clinically isolated aortitis leading to ST elevation myocardial infarction due to an unruptured sinus of Valsalva aneurysm.